2009
DOI: 10.3748/wjg.15.5307
|View full text |Cite
|
Sign up to set email alerts
|

Effects on coagulation factor production following primaryhepatomitogen-induced direct hyperplasia

Abstract: AIM:To investigate the molecular mechanisms involved in coagulation factor expression and/or function during direct hyperplasia (DH)-mediated liver regeneration. METHODS:Direct hyperplasia-mediated liver regeneration was induced in female C57BL/6 mice by administering 1,4-bis[2-(3,5-dichloropyridyloxy)] benzene (TCPOBOP), a representative hepatomitogen. Mice were weighed and sacrificed at various time points [Day 0 (D0: prior to injection), 3 h, D1, D2, D3, and D10] after TCPOBOP administration to obtain liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Differently from the early pattern of F3 gene expression during envenomation, gene expression of Adamts13, Serpinc1 and Proc decreased, whilst that of F10 increased at a later period of envenomation (24 h). Similar results were reported in an experimental model of direct liver hyperplasia and were associated to liver regeneration [77]. This may suggest that the impairment of anticoagulants during envenomation may be aggravated by the decrease in their hepatic synthesis.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 85%
“…Differently from the early pattern of F3 gene expression during envenomation, gene expression of Adamts13, Serpinc1 and Proc decreased, whilst that of F10 increased at a later period of envenomation (24 h). Similar results were reported in an experimental model of direct liver hyperplasia and were associated to liver regeneration [77]. This may suggest that the impairment of anticoagulants during envenomation may be aggravated by the decrease in their hepatic synthesis.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 85%
“…An alternative possibility is that nonparenchymal cells, but hepatocytes, are the main responsive cells for human factor VIII productions. Although the liver has been shown to be the major site of factor VIII production as evidenced by previous liver transplantation clinical experiences (10,13,33), the precise type of liver cells contributing to factor VIII production has not been fully identified (4,6,8,16). In either the case, the present in-mouse hepatocyte propagation system using uPA/SCID mouse might be a valuable tool for the elucidation of cellular mechanism of factor VIII synthesis and production.…”
Section: Discussionmentioning
confidence: 99%
“…Production of coagulation and anticoagulation factors is one of the important functions of the liver, and most of these coagulation-related factors are produced by hepatocytes (4,6,30,31,33). There are various types of congenital bleeding disorders that lack a production of coagulation factor in the liver, showing a symptomatic bleeding tendency.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue factor, a transmembrane glycoprotein, is involved in activating the coagulation cascade and is expressed by tumor cells promoting growth and metastasis (Kasthuri et al, 2009). Tatsumi et al (2009) found decreases in prothrombin and coagulation factors during direct hyperplasia in mice induced by 1,4-bis[2-(3,5-dichloropyridyloxy)] benzene and coagulation disorders associated with cancer are well documented (Falanga et al, 2103;Kvolik et al, 2010).…”
Section: 'Low' Confidence Aopsmentioning
confidence: 99%